Contribuição do exame ultra-sonográfico prognóstico das doenças inflamatórias pélvicas (DIP) - Ribeiro Filho, Ayrton Daniel; Magalhães, Jarbas; Giraldo, Paulo Cézar; Simões, José Antonio; Marussi, Emilio (Brazilian Journal of Sexually Transmitted Diseases, 1997)
Nowadays imaginology has became a high standarc option for diagnosis in medicine. Ultrasonographic exams has became a usefull and routinelly tool for diagnosis and also for therapy. Aiming to study how ultrasound can define prognosis and guide treatments conceming pelvic inflammatory diseases (PID) we analysed retrospectivelly ali womem who underwent surgical or clinicai treatment for PID whithin three years follow up, at an University Women's Hospital in the state of São Paulo, Brazil (CAISM/UNICAMP). Surgical group had frequently at ultrasound larger complex tumors than clinically assisted group. Also homolateral ovary to adenexal tumor was less visuafysed in surgical group. The authors belive that ultrasoimd examination of womem with diagnosis of PID may help therapy options, prognosis and prevew hospital budget, but claim to more studies including transvaginal technics and color doppler exam as suplementary variables to be investigated.